Temperature-Dependent Viscosity Effect on the Peristaltic Transport of (MHD) blood flow Ree-Eyring Fluid Through Porous Medium in an Inclined Asymmetric Channel - Yousif, Rasha; Hayat Adil Ali (Al-Qadisiyah Journal of Pure Science, 2020)
In this article the peristaltic transport of blood flow Ree-Eyring electrically conducting fluid in a porous medium under the effect of magnetohydrodynamic and temperature dependent viscosity through asymmetric channel is examined. Governing flow problem based on momentum, and energy equations are mathematically modelled and investigated in a wave frame of reference moving with the velocity of the wave, by considering the assumption of long wavelength approximation compared to small Renold’s number they simplified and reduced into couple partial differential equations. Exact solution for the temperature profile has been obtained whereas perturbation method employed to find the approximate solution for the stream function. The impact of important physical pertinent parameters on flow phenomena are discussed graphically. The graphs depict that the dimensionless viscosity parameter has mixed effect on velocity profile moreover the two Ree-Eyring fluid parameters and has opposite influence on velocity profile.